Dimensional stability of two impression materials after a 6-month storage period - Francisco Martins; Patrícia Branco; José Reis; Ignacio Barbero Navarro; Paulo Maurício (Medical Journals Sweden, 2017)
Objective: Oral rehabilitation success is enhanced by an accurate and reproducible final impression. The purpose of this study is to evaluate the dimensional changes of a polyether and addition silicone subjected to disinfection and/or sterilization after a long storage period. Material and methods: Ninety samples were obtained from polyether ImpregumTM PentaTM (3M ESPETM, Seefeld, Germany) and 90 of addition silicone ImprintTM 4 PentaTM Putty (3M ESPETM, Seefeld, Germany) according to ISO 4823:2000. The samples of each material were split to form three groups with 30 samples each: a control group, a hypochlorite group (disinfection) and an autoclave group (sterilization). Samples were stored in the Portuguese Institute for Quality for six months at 23 °C. Samples were measured by laser interferometry, according to the Michelson technique before calculating dimensional stability according ISO 4823:2000. A statistical analysis via a three-way mixed ANOVA was performed. Results: Significant shrinkage of ImpregumTM PentaTM was 0.77 ± 0.17% in the control group, 0.42 ± 0.19% in the hypochlorite group and 0.52 ± 0.28% in the autoclave group. For ImprintTM 4 PentaTM Putty, the control group had a shrinkage of 0.42 ± 0.12%, the hypochlorite group 0.36 ± 0.09% and the autoclave group 0.59 ± 0.13%. Conclusions: The long-term storage of samples subjected to disinfection with 5.25% hypochlorite or autoclave sterilization can be used in a clinical setting as the dimensional changes are below the maximum permitted by the ISO 4823:2000, since there are no clinically significant changes in the dimension of the samples during the storage period.